Partial inhibition of the 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 (PFKFB3) enzyme in myeloid cells does not affect atherosclerosis - Tillie, Renée J. H. A.; De Bruijn, Jenny; Perales-Patón, Javier; Temmerman, Lieve; Ghosheh, Yanal; Van Kuijk, Kim; Gijbels, Marion J.; Carmeliet, Peter; Ley, Klaus; Sáez Rodríguez, Julio; Sluimer, Judith C. (Frontiers in cell and developmental biology, 2021)
Background: The protein 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3 (PFKFB3) is a key stimulator of glycolytic flux. Systemic, partial PFKFB3 inhibition previously decreased total plaque burden and increased plaque stability. However, it is unclear which cell type conferred these positive effects. Myeloid cells play an important role in atherogenesis, and mainly rely on glycolysis for energy supply. Thus, we studied whether myeloid inhibition of PFKFB3-mediated glycolysis in Ldlr-/-LysMCre+/-Pfkfb3 fl/fl (Pfkfb3 fl/fl ) mice confers beneficial effects on plaque stability and alleviates cardiovascular disease burden compared to Ldlr-/-LysMCre+/-Pfkfb3 wt/wt control mice (Pfkfb3 wt/wt ). - Methods and Results: Analysis of atherosclerotic human and murine single-cell populations confirmed PFKFB3/Pfkfb3 expression in myeloid cells, but also in lymphocytes, endothelial cells, fibroblasts and smooth muscle cells. Pfkfb3 wt/wt and Pfkfb3 fl/fl mice were fed a 0.25% cholesterol diet for 12 weeks. Pfkfb3 fl/fl bone marrow-derived macrophages (BMDMs) showed 50% knockdown of Pfkfb3 mRNA. As expected based on partial glycolysis inhibition, extracellular acidification rate as a measure of glycolysis was partially reduced in Pfkfb3 fl/fl compared to Pfkfb3 wt/wt BMDMs. Unexpectedly, plaque and necrotic core size, as well as macrophage (MAC3), neutrophil (Ly6G) and collagen (Sirius Red) content were unchanged in advanced Pfkfb3 fl/fl lesions. Similarly, early lesion plaque and necrotic core size and total plaque burden were unaffected. - Conclusion: Partial myeloid knockdown of PFKFB3 did not affect atherosclerosis development in advanced or early lesions. Previously reported positive effects of systemic, partial PFKFB3 inhibition on lesion stabilization, do not seem conferred by monocytes, macrophages or neutrophils. Instead, other Pfkfb3-expressing cells in atherosclerosis might be responsible, such as DCs, smooth muscle cells or fibroblasts.
Gesehen am 29.10.2021